Phytochemical investigation and Pharmacological screening of polyherbal preparation - Sharma, Chandrachud; Sarangdevot, Yuvraj singh; Vyas, Bhupendra (Asian Journal of Pharmaceutical Research and Development, 2024)
The present paper deals with the investigation on comparative physico-chemical and phytochemical screening of five medicinal plants viz., leaves of Gymnema sylvestre, fruits of Momordica charantia, rhizomes of Curcuma longa, seeds of Eugenia jambolana and fruits of Embilica officinalis widely used in the treatment of diabetes. In the present communication comparative results were shown. Various macroscopic, physicochemical and phytochemicals parameters were analyzed and were presented.